Accessibility of Essential Medicines for Children in Sichuan Province of China: A Cross-Sectional Study - Chen, Zhe; Li, Siyu; Choonara, Imti; Zeng, Linan; Jia, Zhi-jun; Cheng, Guo; Yu, Qin; Zhang, Lingli (Frontiers in Pharmacology, 2022)
Background: Essential medicines (EMs) for children are those medicines that satisfy the priority health care needs of children. Access to essential medicines for children is a big challenge, particularly in low- and middle-income countries. Our study aimed to assess the accessibility of EMs for children in the public sector of Sichuan Province of China, based on availability, affordability, and price. Methods: We adopted the modified WHO/HAI standardization methodology to measure the availability, affordability, and prices of 30 EMs for children in 20 public hospitals in nine regions of the Sichuan Province, China. Availability was expressed as the percentage of medicine outlets that stocked surveyed medicines on the day of data collection, and prices were expressed as median price ratio (MPR). Affordability was assessed as the number of Sichuan Province’s daily wages required for the lowest-paid government unskilled worker (USD 11.0310 per day) to purchase one standard treatment of an acute disease or treatment for chronic disease for a month. Results: The mean availability of originator brands (OBs) and lowest priced generics (LPGs) were 9.7% and 46.5% in the public sector. Only 3 MPRs of OBs could be calculated, ranging from 0.55 to 13.37, and the MPRs of LPGs in the public sector ranged from 0.07 to 25.05, with a median MPR of 4.28. 2 OBs and 11 LPGs were priced at more than 1.5 times their international reference prices in the public sector, most of which were injections. Except for cefazolin injection and ceftriaxone injection, most LPGs were affordable for the treatment of childhood diseases in the public sector, as they each cost one or less than one daily wage for the lowest-paid unskilled government worker. Conclusions: The availability of children’s essential medicines was low in surveyed public sector in Sichuan Province, which was similar to previous studies in other provinces of China. The price of most medicines surveyed was higher than their IRPs, especially for some injections. The affordability of most surveyed LPGs was reasonable, except for ceftriaxone injection and cefazolin injection.